Grammatisk informasjon i middels store tospråklege ordbøker. Prinsipp og utfordringar på bakgrunn av arbeidet med Norsk-litauisk ordbok - Berg-Olsen, Sturla; Išganaitytė, Eglė (Nordiske Studier i Leksikografi, 2010)
This article deals with certain questions pertaining to the inclusion of grammatical information in middle-sized bilingual dictionaries. While lexicographers often would like to include quite a lot of information on phonology, morphology and syntax, at least for some users the amount of information can become so large as to hamper the practical use of the dictionary. This is especially the case in dictionaries that aim to be useful for both L1 and L2 speakers. We look at how the editors of the Norwegian-Lithuanian Dictionary tackle this balance in practice, especially focusing on some features that are particular for this language pair, such as variant forms in Norwegian and accentuation and aspect in Lithuanian.